Penerapan Marketing Mix pada Mie Pedas Jajanan Milenialku - Yustika, Gaung Perwira Yustika; Deci Hardiningsih (Haka Vyza Media, 2024)
Marketing mix is used to develop the most basic tactics or methods that can be used as a reference for preparing effective marketing. By implementing an appropriate and correct marketing mix by taking advantage of opportunities to increase sales, the position or position of the marketing mix in the market can be improved or maintained. The purpose of this research is to determine the application of the marketing mix carried out by Mie Pedas Jajanan Milenialku in running its business. The data collection technique in this research uses a qualitative method with a descriptive approach, which takes the form of a description of information that has been obtained from the place of business and is compiled again systematically in the form of a report. Data collection techniques use interview techniques with business owners and also observation. Based on the research results, it shows that My Millenial Snacks Spicy Noodles implements a marketing mix consisting of 4Ps, namely Product, Price, Place and Promotion and has provided good quality for its consumers.